Penguatan Jejaring Kolaborasi Dosen Antar Perguruan Tinggi untuk Optimalisasi Implementasi Tri Dharma - Dyah Erlina Sulistyaningrum; Tri Rettagung Diana; Ria Fajar Nurhastuti; Agus Suryato; Fitriyah Zulfa; Suryadi Suryadi; Maria Yosepin Endah Listyowati; Ayuba Olaniyi Jibril; Imam Rohani; Naylil Mawadatirrohma (BADAN PENERBIT STIEPARI PRESS, 2025)
The implementation of the Tri Dharma of Higher Education—education, research, and community service—continues to face various challenges, particularly due to limited resources and a lack of synergy among lecturers from different institutions. This study aims to examine strategies for strengthening inter-university lecturer collaboration networks as a means to optimize the implementation of the Tri Dharma. A qualitative method was used, with a case study approach involving several universities in Indonesia that have established inter-institutional collaborations. Data were collected through in-depth interviews, observations, and document analysis, then analyzed thematically. The findings indicate that structured collaborative networks can enhance teaching efficiency, strengthen the quality of joint research, and broaden the impact of community service programs. Key supporting factors include shared vision, institutional support, and effective communication platforms. The implications of this study highlight the importance of institutional policies that promote cross-university collaboration as a sustainable strategy to empower lecturers in carrying out the Tri Dharma more effectively and with greater impact.